The Expanded Role of the Federal Cabinet in Pipeline Projects. A Case Study of TC Energy's 2021 NGTL System Expansion - Harrison, Rowland, Q.C. (Université d'Ottawa | University of Ottawa, 2021)
This study from the University of Ottawa’s Positive Energy program examines cabinet’s review of the 2021 NGTL System Expansion Project following recommendations from the Canada Energy Regulator. The study, authored by Rowland Harrison, Q.C., Positive Energy Faculty Affiliate and former NEB board member, suggests that tensions may arise between two fundamental public responsibilities with respect to reviewing proposals for major resource development projects. The first of these is to fulfill, and respect, the requirements of the constitutional duty of the Crown to consult and, where appropriate, accommodate Indigenous peoples. The second is to maintain the integrity and effectiveness of the applicable regulatory framework, particularly by being transparent, and by complying with the requirements of procedural fairness.
Keywords: Indigenous Rights; Indigenous people; Energy policy; Energy regulation; Duty to Consult; Reconciliation; Positive Energy; Oil and Gas; Canada Energy Regulator; National Energy Board; Energy Infrastructure; Pipelines